1987
DOI: 10.1111/j.1432-1033.1987.tb13407.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Lewis fucolipid antigens in human colorectal carcinoma cells. Partial characterization of LcOse4Cer and H-1 fucolipid fucosyl transferase acceptor activities

Abstract: Purified glycolipids were tested for their ability to serve as acceptors of ['4C]fucose from GDP-['4C]fucose as catalyzed by cell-free extracts and purified membrane fractions of human colorectal carcinoma cells, SW1116, cultured in serum-free medium. Purified lactotetraosyl ceramide (GalP1+3GlcNAcPl+ 3GalP1+4Glc-Cer or LcOse4Cer) and H-1 glycolipid (Fucal+2Gal~1+3GlcNAc~1+3Gal~1+4Glc-Cer or IV2 FucaLcOse4Cer) stimulated incorporation of radioactivity into lipid-soluble glycolipid at a rate greater than ten ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Assay for Glycolipid-Dependent Sialyltransferase. Purified membrane fractions containing sialyltransferase activity were obtained from human colorectal carcinoma SW1116 cells by sucrose density centrifugation as previously described (Liepkans & Larson, 1987). Standard conditions for incubation were the following: 70 gg of taurocholate (sodium salt) dissolved in chloroform/methanol (2/1) was dried with 0.2-5 gg of LcOse4Cer or test glycolipid in a conical assay tube; 30-45 gL of (final concentrations) cacodylate (0.15 mM), sucrose (0.3 M), MgCl2 (1 mM), and CDP-choline or ATP (0.5 mM) were then added.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Assay for Glycolipid-Dependent Sialyltransferase. Purified membrane fractions containing sialyltransferase activity were obtained from human colorectal carcinoma SW1116 cells by sucrose density centrifugation as previously described (Liepkans & Larson, 1987). Standard conditions for incubation were the following: 70 gg of taurocholate (sodium salt) dissolved in chloroform/methanol (2/1) was dried with 0.2-5 gg of LcOse4Cer or test glycolipid in a conical assay tube; 30-45 gL of (final concentrations) cacodylate (0.15 mM), sucrose (0.3 M), MgCl2 (1 mM), and CDP-choline or ATP (0.5 mM) were then added.…”
Section: Methodsmentioning
confidence: 99%
“…Two milliliters of affinity gel, CMP-agarose (Sigma) or LcOse4-fractogel (Bio-Carb, Lund, Sweden) were washed in CST buffer (0.025 M cacodylate, 0.050 M NaCl, 0.05% taurocholate) by suspension and centrifugation at lOOOg, 6 X 6 mL. Human colorectal carcinoma cells cultured in serum-free medium were obtained as described previously (Liepkans et al, 1985): the cells were homogenized and sonicated (15 s, 4 bursts at +4 °C) in CSM buffer (0.2 M cacodylate, 0.2 M sucrose, 1 mM MgCl2) and then centrifuged at lOOOg for 1 h. The pellet of nuclei unbroken cells and debris was discarded, and the supernatant was applied to a sucrose gradient (p = 1.10-1.18) in CSM buffer (Liepkans & Larson, 1987). After the sucrose gradient, the total membranes from this centrifugation (excluding the pellet) were recovered by dilution 2-fold with 0.15 M cacodylate, pH 6.2, and centrifugation at 150000g for 2 h. The resulting final microsomal pellet, which was devoid of mitochondria, was suspended in CST buffer by repeated gentle regurgitation with sterile Pasteur pipets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yazawa and Furukawa [28] showed no formation of Leb from Lea in the saliva from O secretor donors. It was also shown that the direct precursor of Leb fucolipid was H type 1 fucolipid and LeJ was not a good substrate for the synthesis of Leb fucolipid in extracts of purified membrane fractions of colorectal carcinoma cells, SW1116 [43]. On the other hand, it has been reported that extracts of microsomal fractions of human gastric mu cosa and gastric carcinoma cell line KATO III were active in forming Leb-glycolipid from Led-glycolipid [44,45], al though an activity to form Ley from Lex was not detected in KATO III cells [45], Recently, Yazawa et al [46] have also demonstrated the activity that catalyzed the forma tion of Leb from Lea and of Ley from Le' in a Triton X-100 extract of colon cancer tissue and suggested the presence of a new a-2-L-fucosyltransferase.…”
Section: Discussionmentioning
confidence: 99%